2017
DOI: 10.1186/s12879-017-2443-4
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the geographical risks of wild and vaccine-derived poliomyelitis outbreaks in Africa and Asia

Abstract: BackgroundThe international spread of wild poliomyelitis outbreaks continues to threaten eradication of poliomyelitis and in 2014 a public health emergency of international concern was declared. Here we describe a risk scoring system that has been used to assess country-level risks of wild poliomyelitis outbreaks, to inform prioritisation of mass vaccination planning, and describe the change in risk from 2014 to 2016. The methods were also used to assess the risk of emergence of vaccine-derived poliomyelitis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…While the presence of an outbreak in the last 4 years was associated with disease in the next year in Models 2 and 3, NP-AFP dose histories were not associated with disease in the following year after adjusting for DTP3 coverage. This is in line with Voorman and Lyons (2016) who showed systematic bias in the ascertainment of NP-AFP dose histories, and with O’Reilly et al (2017) who also found a lack of association [ 17 , 23 ]. In both cases, results for all other variables were not materially different (see S1 File ).…”
Section: Resultssupporting
confidence: 85%
“…While the presence of an outbreak in the last 4 years was associated with disease in the next year in Models 2 and 3, NP-AFP dose histories were not associated with disease in the following year after adjusting for DTP3 coverage. This is in line with Voorman and Lyons (2016) who showed systematic bias in the ascertainment of NP-AFP dose histories, and with O’Reilly et al (2017) who also found a lack of association [ 17 , 23 ]. In both cases, results for all other variables were not materially different (see S1 File ).…”
Section: Resultssupporting
confidence: 85%
“… Abbreviations: DEB, differential-equation-based model; DES, discrete-event simulation model; IB, individual-based model; IC, Imperial College; IDM, Institute for Disease Modeling; IPV, inactivated poliovirus vaccine; iVDPVs, immunodeficiency-associated vaccine-derived poliovirus; KRI, Kid Risk, Inc.; OPV, oral poliovirus vaccine; SC, stochastic compartmental model; SIAs, supplementary immunization activities. Notes a Two papers included one middle author from IDM [ 100 , 109 ]. b One author on three papers now at the London School of Hygiene and Tropical Medicine [ 116 , 117 , 127 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 2011, to explore the widespread transmission of WPVs in Africa, IC applied a statistical model that identified the proximity to the continued transmission in Nigeria and poor performance of national immunization programs in some neighboring countries as risk factors for transmission of reintroduced WPVs in Africa [ 93 ]. In 2017, IC revisited this topic for both Africa and Asia, concluded that low population immunity represented a key risk factor for WPV or cVDPV transmission, and recommended maintenance or improvement of vaccination in the high-risk areas it identified [ 109 ]. In 2015, IC applied a statistical model to estimate the effectiveness of SIAs using nonpolio AFP cases reported for children <2 years old in Pakistan, which showed temporal changes in coverage and identified some under-vaccinated populations [ 110 ].…”
Section: Summary Of Publications Reviewedmentioning
confidence: 99%
“…Furthermore, with data about fecal–oral contamination (whether from studies of other enteric diseases or sanitation), our model can be calibrated to predict transmission rates in the absence of poliovirus and may thus have predictive value far into the post-cessation future. To go from outbreak risk categorization to risk quantification, continuing work to better understand the relationships between local and nonlocal transmission is needed [ 129 131 ].…”
Section: Discussionmentioning
confidence: 99%